Factors influencing the adoption of Islamic banking product: a review of literature - Abdullahi, Abdurrahman; Othman, Anwar Hasan Abdullah; Kassim, Salina (2020)
The aim of this paper is to review empirical studies that examined the factors influencing the adoption of Islamic banking products and services with a view to making suggestions to the stakeholders in the Islamic finance services industry (IFSI) in Nigeria. The paper employed the literature review methodology to synthesize research findings in the study area. Most of the studies reviewed showed that Attitude, subjective norms and perceived behavioral control positively and significantly influence the use of Islamic banking products. Others influencing factors include knowledge, awareness, compatibility, religiosity and perceived government support. The paper recommended that Islamic banks in Nigeria should develop robust marketing strategies that will boost the beliefs and attitudes of consumers of banking services, at the same time decreasing their perceived risks. In addition, they should increase customers’ awareness through effective communication, as well as develop low cost Islamic financial products that will improve competitiveness.